Association between protein intake and changes in renal function among Japanese community‐dwelling older people: The SONIC study. Issue 4 (10th February 2022) - Sekiguchi, Toshiaki; Kabayama, Mai; Ryuno, Hirochika; Tanaka, Kentaro; Kiyoshige, Eri; Akagi, Yuya; Godai, Kayo; Sugimoto, Ken; Akasaka, Hiroshi; Takami, Yoichi; Takeya, Yasushi; Yamamoto, Koichi; et al.
Abstract : Aim: The aim of this study was to clarify the association between dietary protein intake and decline in the estimated glomerular filtration rate (eGFR) among Japanese older adults. Methods: We used the data of the Septuagenarians, Octogenarians and Nonagenarians Investigation with Centenarians (SONIC) study, an ongoing narrow‐age range cohort study: 69–71 years, 79–81 years and 89–91 years. The outcome variable, change in eGFR, was estimated from serum creatinine measured at the baseline and 3‐year follow up, and the exposure variable, protein intake, was calculated using the brief‐type self‐administered diet history questionnaire at the baseline. Associations between eGFR change and protein intake were determined by multiple linear regression analysis. Results: The mean eGFR change per year was −1.89 mL/min/1.73 m 2 . The mean protein intake was 1.50 g/kg/day. The results of this study showed that there was no significant association between protein or animal protein intake and change in eGFR per year in the entire population of participants, including the very elderly, but there was a significant positive association in those whose renal function fell into chronic kidney disease stage G3 or G4. Conclusions: Protein intake among community‐dwelling older adults was not associated with lower eGFR, and for older chronic kidney disease patients, protein and animal protein intakes were more beneficial in maintaining eGFR. The results provide evidence that protein intake should not be restricted for older patients with chronic kidney disease, including the very elderly. Geriatr Gerontol Int 2022; 22: 286–291 .